2007
DOI: 10.2174/157019307779815929
|View full text |Cite
|
Sign up to set email alerts
|

Benzo-Annelated Cyclic Polysulfides

Abstract: The preparation, structure, and reactivity of benzo-annelated cyclic polysulfides, which principally contain five-and seven-membered rings, are described together with the chemistry of their related compounds. The stereochemistry of benzopentathiepins and the electrochemistry of benzotrithioles are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Syntheses of trithiols have recently been reviewed [115]. The corresponding trithiolium radical cation 21 +• can be prepared by chemical oxidation of 21 with SbCl 5 [116][117][118].…”
Section: 23-trithiolium Radical Cationmentioning
confidence: 99%
“…Syntheses of trithiols have recently been reviewed [115]. The corresponding trithiolium radical cation 21 +• can be prepared by chemical oxidation of 21 with SbCl 5 [116][117][118].…”
Section: 23-trithiolium Radical Cationmentioning
confidence: 99%
“…Recently, considerable attention has been focused on three or four membered dichalcogenide ring systems, due to their strained structures and high reactivities . The smallest cyclic disulfide, 1,2-dithiiran, was first isolated and reported by Ishii et al in 1994 .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many related compounds have been prepared, and studies of their structures and reactivities have accumulated. In addition, both saturated and unsaturated four membered cyclic disulfides, the 1,2-dithietanes and 1,2-dithietes, have been investigated by many organic chemists . On the basis of these studies, it is known that these ring systems are quite unstable and that 1,2-dithiete incorporates more steric strain than does 1,2-dithietane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound constructed by the reaction of t BuPcTiO with tetrahydroxy‐ p ‐benzoquinone in a 2:1 ratio is an unsymmetric double‐decker‐type molecule. As a result of our continuing study of several cyclic oligosulfides,9 we recently reported the preparation and the electrochemical and optical properties of octakis(benzylthio)phthalocyanine ( PcSBn ), tetrakis( o ‐xylylenedithio)phthalocyanines ( PcSXyl ), and related derivatives 10. In relation to the application of phthalocyanine to new functional materials, it is significant that a Q‐band absorption lies in the near‐infrared region of the UV/Vis absorption spectrum.…”
Section: Introductionmentioning
confidence: 99%